Cluster Program to Reduce Children's Social Resistance - Emilda Sulasmi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This study discusses to discuss the social that occurs in society. The gap that occurs is marked by the separation of a group of young people who are displayed like rock n roll taken while holding hands in the window of a car, like beggars but they are still young, like buskers but all eccentric. This phenomenon is seen at red lights, crossroads, highway bridges, terminals and others. This study uses qualitative research by studying phenomenology in the city of Bengkulu. Data collection techniques used in this study were observation, interviews, and documentation, using descriptive analysis with interactive analysis models. The results obtained are the Bengkulu city government through the Social Service which implements a social problems program (PMKS), the program includes: community-based social education, by providing opportunities for punk school children with a program package, providing entrepreneurial safety training and conducting ongoing supervision. This program succeeded in changing the city of Bengkulu which is free of punk children and returning punk children can be anticipated with an ongoing program.